Bundle Branch Reentrant Ventricular Tachycardia in a Patient with the Brugada Electrocardiographic Pattern - Mazur, Alexander (Ann Noninvasive Electrocardiol, 2003)
A 55‐year‐old, previously healthy man presented with an episode of wide QRS tachycardia that had left bundle branch morphology and left superior axis. His electrocardiogram in sinus rhythm showed characteristic Brugada pattern with coved type ST‐segment (J‐point) elevation in leads V(1)–V(2), mild QRS widening of 110 ms, and left axis deviation. The mechanism of the tachycardia was shown to be bundle branch reentry. Baseline H‐V interval of 68 ms additionally lengthened to 119 ms after intravenous procainamide administration indicating significant conduction system disease. The tachycardia was no longer inducible after successful ablation of the right bundle branch.